โปรแกรมกิจกรรมโดยประยุกต์แนวคิดการจัดการศึกษาแบบเชิญชวนที่มีต่อความตระหนักรู้และการปฏิบัติเพื่อป้องกันฝุ่น PM 2.5 ของนักเรียนประถมศึกษา - ประภาวรินทร์ รัชชประภาพรกุล (มหาวิทยาลัยการกีฬาแห่งชาติ, 2022)
Purposes: To study the effects of an activity program applying invitational education approach on the awareness and practices to prevent PM 2.5 in primary school students. Methods: The subjects consisted of 40 third grade students, divided equally into 2 groups, 20 students for the experimental group, and 20 students in the control group. The research instruments were the activity program applying invitational education approach on the awareness and practices to prevent PM 2.5 consisting of 5 activities that had the index of congruence scores between 0.92 - 0.96, the average mean of index of congruence was 0.95, and the awareness and practices assessment form with IOC 0.98 and 0.96, and reliabilities were 0.81 and 0.90. The research was conducted for 8 weeks, 2 days a week, 50 minutes per day. The data were analyzed by mean, standard deviation and t - test.